2022
DOI: 10.3390/nu14040831
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Dairy Foods and Cardiovascular Disease: A Systematic Review

Abstract: Limited consumption of dairy foods and use of low-fat products is recommended for cardiovascular (CV) prevention; however, other features besides fat content modulate their metabolic effects. We analyze updated evidence on the relationship of different dairy products (low/full-fat dairy, milk, cheese, yogurt) with CVD by reviewing meta-analyses of cohort studies and individual prospective cohort studies with CV hard endpoints (CVD/CHD incidence/mortality), together with meta-analyses of randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 85 publications
1
16
0
Order By: Relevance
“…This difference between North Europe and low-middle countries might be partly due to higher milk consumption in North Europe (non-fermented milk mean: 278 g/day in the MDCS) compared with lowmiddle countries (milk mean: <100 g/day) [10]. Furthermore, in line with previous studies [41], the current study indicated inverse associations of fermented milk intake with incident CVD and CVD mortality. These findings further highlight that non-fermented milk and fermented milk may have distinct associations with the risk of CVD events.…”
Section: Discussionsupporting
confidence: 89%
“…This difference between North Europe and low-middle countries might be partly due to higher milk consumption in North Europe (non-fermented milk mean: 278 g/day in the MDCS) compared with lowmiddle countries (milk mean: <100 g/day) [10]. Furthermore, in line with previous studies [41], the current study indicated inverse associations of fermented milk intake with incident CVD and CVD mortality. These findings further highlight that non-fermented milk and fermented milk may have distinct associations with the risk of CVD events.…”
Section: Discussionsupporting
confidence: 89%
“…Their findings indicated that healthier plant-based diets are associated with a lower incidence of hypertension and type-2 diabetes, especially among those with a family history of the disease [ 6 ]. Moreover, in this Special Issue, under the area of diet and disease risk, is a systematic review written by Giosue and colleagues [ 7 ]. These researchers evaluated published studies that examine dairy product consumption and disease risk with a focus on cardiovascular disease, while also addressing its association with factors that contribute to disease risks such as body weight, fasting blood glucose, glycated hemoglobin, blood pressure, and inflammation to name a few.…”
mentioning
confidence: 99%
“…Several health benefits have been related to yogurt consumption, including strengthening the immune system, improvement of the digestive function, and protection against colon cancer and Helicobacter pylori infection [ 5 ]. Moreover, diverse in vivo studies have suggested that yogurt consumption may have some protective effects against the onset of chronic diseases, especially cardiovascular diseases [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%